THYMIC REGRESSION AND LEUKEMIC INFILTRATION DYNAMICS IN ACUTE LYMPHOBLASTIC LEUKEMIA: PROSPECTIVE EVALUATION BY 18F-FDG PET/CT AND DIFFUSION-WEIGHTED MRI WITH CLINICO-MORPHOLOGICAL AND PROGNOSTIC CORRELATION - Ruzieva Maftuna Bahtiyor qizi; Allaberganov Dilshod Shavkatovich (THE PLACE AND ROLE OF TURKEY AND THE NEAR REGION IN THE PROCESSES OF SCIENTIFIC, SOCIAL, AND CULTURAL DEVELOPMENT, 2025)
To quantitatively evaluate the dynamics of thymic involution and residual leukemic infiltration in T-lineage and B-lineage acute lymphoblastic leukemia (ALL) using multimodal imaging (18F-FDG PET/CT and diffusion-weighted MRI) and to determine their predictive value for early therapeutic response and long-term outcome. Materials and Methods: Prospective cohort of 46 patients (27 T-ALL, 19 B-ALL; age 3–42 years, median 14.8) diagnosed 2022–2025. All patients underwent baseline and day 22–28 18F-FDG PET/CT and 3T thoracic MRI (DWI b=0-1000 s/mm², ADC mapping). Thymic volume (3D volumetric segmentation), SUVmax, TLG, ADCmean, and ADCmin were measured. Thymic biopsies/resections (n=18) were analyzed by H&E and IHC (TdT, CD1a, CD3, CD99, Ki-67). MRD was assessed by 8-color flow cytometry (10⁻⁴ sensitivity). Results: At diagnosis, median thymic volume in T-ALL was 48.7 cm³ (range 9.2–112.4) vs 8.4 cm³ in B-ALL (p<0.001); SUVmax 9.8 ± 3.4 vs 2.1 ± 0.9 (p<0.001). After induction, thymic volume decreased by 64.2 ± 14.8 % in T-ALL and 81.7 ± 11.2 % in B-ALL. ADCmean increased from 0.74 ± 0.12 to 1.41 ± 0.18 × 10⁻³ mm²/s (p<0.001). Thymic volume reduction ≥58 % and ADCmean ≥1.18 × 10⁻³ mm²/s predicted MRD negativity with 91 % sensitivity and 88 % specificity (AUC=0.94). Combined criterion (baseline SUVmax ≥8.5 + ADCmean ≤0.82) identified a high-risk group with 2-year overall survival of 61 % vs 92 % in the low-risk group (log-rank p=0.012). Histopathological correlation revealed 89.4 ± 7.2 % blast infiltration in T-ALL with strong inverse correlation to ADCmean (r=−0.86, p<0.001). Conclusion: The thymus represents the primary leukemic reservoir in T-ALL. Multimodal PET/CT and DWI-MRI accurately monitor thymic regression kinetics and serve as powerful, non-invasive early response and prognostic biomarkers superior to conventional morphology. These parameters enable risk-stratified therapy adaptation, potentially improving outcomes in high-burden disease.